Biologics targeting IL-17 and IL-23 maintain stability in patients with psoriasis during COVID-19 infection: a case-control study - Huang, Dawei; Yu, Yingyuan; Lu, Jiajing; Tan, Fei; Shi, Yuling (Frontiers in Medicine, 2023)
Background Psoriasis is a chronic and refractory skin disease. The emergence of biologics provides more options for the treatment of psoriasis, but the COVID-19 pandemic poses challenges for the management of psoriasis. Objectives The purpose of this study was to investigate the effect of different biologics on the stabilization of psoriasis during COVID-19 infection in China. Methods This is a single-center, observational, retrospective, case–control study. Using our database, we conducted a remote dermatologic study by means of questionnaire follow-up or telephone follow-up to collect general information of patients, information related to COVID-19 infection and conditions of psoriasis for comparison and further analysis between groups. Results Our study ultimately included 274 patients for analysis. We found that the patients in this collection had mild symptoms of COVID-19 infection, and only 13 of them needed to go to the hospital for medical treatment. Further studies found that in biologics, relative to tumor necrosis factor-α inhibitors (TNF-αi), interleukin-17 inhibitors (IL-17i) and interleukin-23 inhibitors (IL-23i) are both protective factors in flare-up of psoriasis [IL-17i: OR (95% CI) = 0.412 (0.189–0.901); IL-23i: OR (95% CI) = 0.291 (0.097–0.876)]. In addition, we also found that the proportion of people with increased psoriasis developing long COVID-19 increased, and we speculated that increased psoriasis may be a potential risk factor for long COVID-19. Conclusion Our study showed that the use of IL-17i and IL-23i was a protective factor for psoriasis compared with TNF-αi, and could keep the psoriasis stable.